The utrophin and dystrophin genes share similarities in genomic structure. - Pearce, M; Blake, D; Tinsley, J; Byth, B; Campbell, L; Monaco, A; Davies, K (1993)
Utrophin and dystrophin are highly homologous proteins which are reciprocally expressed in DMD (Duchenne muscular dystrophy) muscle. The remarkable similarity of these proteins suggests that they may play a similar cellular role in some circumstances; if this were the case then utrophin may be capable of replacing dystrophin in DMD patients. In this paper we show that the genomic structure of the utrophin gene is similar to the dystrophin gene, further exemplifying the relatedness of the two genes and their gene products. We have constructed a 1.25 Mb contig of eight yeast artificial chromosome (YAC) clones covering the utrophin gene located on chromosome 6q24. Utrophin is encoded by multiple small exons spanning approximately 900 kb. The distribution of exons within the genomic DNA has similarities to that of the dystrophin gene. In contrast to dystrophin, the utrophin gene has a long 5' untranslated region composed of two exons and a cluster of unmethylated, rare-cutting restriction enzyme sites at the 5' end of the gene. Similarities between the genomic structure suggest that utrophin and dystrophin arose through an ancient duplication event involving a large region of genomic DNA.